Simulation of efficient irrigation management strategies for grain sorghum production over different climate variability classes. (March 2019) - Kothari, Kritika; Ale, Srinivasulu; Bordovsky, James P.; Thorp, Kelly R.; Porter, Dana O.; Munster, Clyde L.
Abstract: The Texas High Plains (THP) is a productive agricultural region, and it relies heavily on the exhaustible Ogallala Aquifer for irrigation water for crop production. Efficient use of irrigation water is critical for the sustainability of agriculture in the THP. Grain sorghum is one of the major crops grown in the region, and it is known for its drought tolerance and lower water requirement compared to other cereal crops such as corn. In this study, the CERES-Sorghum and CROPGRO-Cotton modules of the Decision Support System for Agrotechnology Transfer (DSSAT) were evaluated using data from cotton-sorghum rotation experiments at Halfway, Texas over a period of nine years (2006–2014). The evaluated CERES-Sorghum model was then used to identify the optimum (i) initial soil moisture at planting (ISM); (ii) threshold to start irrigation (ITH); (iii) threshold to terminate irrigation; and iv) deficit/excess (DFI) irrigation strategy for grain sorghum production based on simulated sorghum yield, irrigation water use efficiency (IWUE), and grain water use efficiency (WUE). In addition, the effect of weather conditions on simulated strategies was elucidated by dividing the long-term (1977–2016) weather data into cold, warm, wet, dry, and normal climate variability classes based on the 33rd and 66th percentiles of growing season temperature and precipitation. The DSSAT model adequately simulated the grain sorghum and seed cotton yields during calibration (average Percent Error (PE) of 1.3% (sorghum) and 3.4% (cotton)) and evaluation (average PE of −2.2% (sorghum) and −10.5% (cotton)). The results from long-term simulations indicated that weather conditions played a key role in selecting appropriate irrigation management strategies. Under normal/cold/wet weather, ISM of 75% available water holding capacity (AWC), ITH of 50%, and DFI 85% were found to be adequate for irrigated grain sorghum production. However, in warm/dry weather, ISM of 75%, ITH 60%, and DFI at 100% reduced sorghum yield loss. Highlights: CERES-Sorghum model was used to suggest optimum irrigation thresholds for sorghum. Weather conditions effected sorghum yields more when compared to irrigation strategies. Maintaining soil water at planting at 75% of available water content (AWC) optimized irrigation water use efficiency. Initiating irrigation at 50% AWC and stopping it at 85% AWC is adequate under normal, colder and wet conditions. Under warm-dry weather, initiating irrigation at 60% AWC and stopping it at 100% AWC is advisable.